Caprylic acid fractionation of hyperimmune horse plasma: description of a simple procedure for antivenom production - Rojas Céspedes, Gustavo (1994)
A simple methodology for hyperimmune horse plasma fractionation, based on caprylic acid precipitation, is described. Optimal conditions for fractionation were studied; the method gives best results when concentrated caprylic acid was added to plasma, whose pH had been adjusted to 5.8, until a final caprylic acid concentration of 5% was reached. The mixture was vigorously stirred during caprylic acid addition and then for 60 min; afterwards the mixture was filtered. Non-immunoglobulin proteins precipitated in these conditions, whereas a highly enriched immunoglobulin preparation was obtained in the filtrate, which was then dialysed to remove caprylic acid before the addition of NaCl and phenol. Thus, antivenom was produced after a single precipitation step followed by dialysis. In order to compare this methodology with that based on ammonium sulfate fractionation, a sample of hyperimmune plasma was divided into two aliquots which were fractionated in parallel by both methods. It was found that caprylic acid-fractionated antivenom was superior in terms of yield, production time, albumin/globulin ratio, turbidity, protein aggregates, electrophoretic pattern and neutralizing potency against several activities of Bothrops asper venom. Owing to its efficacy and simplicity, this method could be of great value in antivenom and antitoxin production laboratories.